LGP2 plays extensive roles in modulating innate immune responses in Ctenopharyngodon idella kidney (CIK) cells. Issue 1 (March 2015) - Chen, Xiaohui; Yang, Chunrong; Su, Jianguo; Rao, Youliang; Gu, Tianle
Highlights Overexpression of CiLGP2 induced CiRIG-I but inhibited CiIPS-1 expression in CIK cells. CiLGP2 cooperated with CiMDA5 to enhance antiviral signaling against GCRV. CiLGP2 impaired RLR-dependent antiviral responses to poly(I:C). CiLGP2 altered the expression patterns of RLR genes after LPS treatment. CiLGP2 significantly enhanced the RLR signaling upon PGN stimulation.